2019
DOI: 10.1183/13993003.02408-2018
|View full text |Cite
|
Sign up to set email alerts
|

CCSP counterbalances airway epithelial-driven neutrophilic chemotaxis

Abstract: Club cell secretory protein (CCSP) knockout mice exhibit increased airway neutrophilia, as found in chronic obstructive pulmonary disease (COPD). We therefore investigated whether treating COPD airway epithelia with recombinant human CCSP (rhCCSP) could dampen exaggerated airway neutrophilia.Control, smoker and COPD air–liquid interface (ALI) cultures exposed to cigarette smoke extract (CSE) were treated with and without rhCCSP. The chemotactic properties of the supernatants were assessed using Dunn chambers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…In vitro studies using air-liquid interface cell cultures showed that COPD airway epithelia exhibited enhanced chemotactic activity. Recombinant human club cell secretory protein can neutralize CXCL8 and thereby prevent neutrophil recruitment to the airways [ 172 ]. The CXCR2 antagonist MK-7123 improved lung function in patients with moderate to severe COPD, but long-term treatment was associated with a reduction in circulating neutrophils and a slightly increased rate of infections [ 173 ].…”
Section: Neutrophils In Chronic Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies using air-liquid interface cell cultures showed that COPD airway epithelia exhibited enhanced chemotactic activity. Recombinant human club cell secretory protein can neutralize CXCL8 and thereby prevent neutrophil recruitment to the airways [ 172 ]. The CXCR2 antagonist MK-7123 improved lung function in patients with moderate to severe COPD, but long-term treatment was associated with a reduction in circulating neutrophils and a slightly increased rate of infections [ 173 ].…”
Section: Neutrophils In Chronic Inflammationmentioning
confidence: 99%
“… [ 173 ] IL-8 (CXCL8) neutralization with rhCCSP COPD In vitro air-liquid interface cell culture Reduced neutrophil chemotaxis. [ 172 ] CCR2 antagonist (RS102895) daily at ZT17 Atherosclerosis Apoe−/− mice fed a high-fat diet Reduced arterial myeloid cell adhesion, atherosclerotic lesion formation and macrophage accumulation. [ 201 ] Canakinumab (monoclonal antibody targeting IL-1β) Atherosclerosis Randomized trial in patients with prior history of MI and high-sensitivity C-reactive protein Reduction in cardiovascular events.…”
Section: Neutrophils In Chronic Inflammationmentioning
confidence: 99%
“…147 CCSP may also directly neutralize IL-8, therefore damping neutrophil chemotaxis. 148 Club cell secretory protein-16 (CC16) (−/−) mice are more susceptible to CS effects, with induction of a COPD phenotype characterized by greater emphysema, airway remodelling, increased airway MUC5AC expression, alveolar cell apoptosis and inflammation. 142 Delivering CC16 protein to the airways of CC16−/− mice induced airway immunostaining for CC16 and rescued the development of COPD-like lung lesions 142 via a yet-to-be elucidated mechanism.…”
Section: Club Cellsmentioning
confidence: 99%
“…In vitro epithelial club cell 10‐kDa protein (CC10) gene transduction may inhibit IL‐1β‐induced IL‐8 expression and nuclear factor κB (NF‐κB) activation 147 . CCSP may also directly neutralize IL‐8, therefore damping neutrophil chemotaxis 148 . Club cell secretory protein‐16 (CC16) (−/−) mice are more susceptible to CS effects, with induction of a COPD phenotype characterized by greater emphysema, airway remodelling, increased airway MUC5AC expression, alveolar cell apoptosis and inflammation 142 .…”
Section: Mechanisms Of Copdmentioning
confidence: 99%
“…Reduced mucous hydration [24] Reduced cilia beat frequency [24] Increased viral infections [32] Increased mucous retention Increased BMI Increased ACE2 expression [34] Increased CD11b, CD16, CXCR2 expression [19] Abnormal epithelial differentiation [23] Increased activity may be important to protect lungs from unwanted tissue damage during inflammation and club cell secretory protein may be important in this regard. KNABE et al [38] reported that club cell secretory protein reduces neutrophil chemotaxis towards cigarette smoke-induced CXCL8 release from bronchial epithelial cells. Similarly, STARKEY et al [39] demonstrated that cigarette smoke-exposed interleukin (IL)-22 deficient mice have reduced lung neutrophil numbers, and are protected from airway fibrosis and alveolar tissue destruction, suggesting a role for IL-22 in neutrophil infiltration.…”
Section: Cigarette Smokementioning
confidence: 99%